Risk of post-treatment Lyme disease in patients with ideally-treated early Lyme disease: A prospective cohort study. (March 2022) - Aucott, John N.; Yang, Ting; Yoon, Isaac; Powell, Debra; Geller, Steven A.; Rebman, Alison W.
Highlights: Fourteen percent of patients met criteria for post-treatment Lyme disease (PTLD). Persistent fatigue and pain occurred despite early diagnosis and prompt treatment. Differences were significant after controlling for co-morbidities and other factors. Abstract: Purpose: Post-treatment Lyme disease (PTLD) is characterized by patient-reported symptoms after treatment for Borrelia burgdorferi infection. The primary aim of this study was to assess whether participants with a history of Lyme disease (LD) would be more likely to meet criteria for PTLD than those without a history of LD. Methods: We conducted a longitudinal, prospective study among 234 participants with and 49 participants without prior LD. All completed survey metrics for fatigue, pain, sleep, depression, and quality of life. An operationalized PTLD definition was applied to both cohorts, and the distributions of clinical outcomes and symptoms were examined. Results: In total, 13·7% of participants with a history of prior LD met criteria for PTLD compared with 4·1% of those without a history of prior LD. Participants with prior LD were approximately 5·28 times as likely to meet PTLD criteria compared with those without prior LD ( p  = 0·042) and had 8-15 times as high odds of reporting moderate or severe fatigue and muscle pain ( p  = 0·002, 0·047, respectively). Risk of meeting PTLD criteria was also independently increased among females and those with higher exposure to previous traumatic life events. Conclusion: Participants ideally diagnosed and treated for prior LD reported more symptoms on standardized surveys and were more likely to meet criteria for PTLD than those without prior LD.